2020
DOI: 10.1080/09593330.2020.1720303
|View full text |Cite
|
Sign up to set email alerts
|

A Study on removal of Methylene Blue dye by photo catalysis integrated with nanofiltration using statistical and experimental approaches

Abstract: In this work, the removal of Methylene Blue dye from the synthetic textile effluent has been investigated using a hybrid system (photocatalysis and nanofiltration). The Commercial ZnO powder was used as a catalyst in the photocatalytic operation. Response surface methodology (RSM) was employed to optimize the various operating parameters such as pH, catalyst loading and time duration and this optimization has enhanced the decolorization efficiencies.The results were compared and contrasted with the individual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…The aim of this present study is to develop the RSM model to optimise the hydroxyl value of bio-polyol from methyl oleate. To the best of the knowledge of the authors, there is no reported study regarding the optimisation of the reaction condition for the epoxide ring opening reaction using RSM, even though it is used as a statistical tool for the optimisation technique in other chemistry areas such as extraction of flavonoids [ 23 ] and waste water treatment [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…The aim of this present study is to develop the RSM model to optimise the hydroxyl value of bio-polyol from methyl oleate. To the best of the knowledge of the authors, there is no reported study regarding the optimisation of the reaction condition for the epoxide ring opening reaction using RSM, even though it is used as a statistical tool for the optimisation technique in other chemistry areas such as extraction of flavonoids [ 23 ] and waste water treatment [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the flux of the membrane was basically constant (Figure e), indicating that the membrane could effectively remove the intercepted dye molecules with the assistance of Ag/AgBr/AgVO 3 . As shown in Figure S4, the Ag/AgBr/AgVO 3 -NF membrane showed satisfactory dye removal efficiency relative to the membranes reported in the literature. …”
Section: Resultsmentioning
confidence: 74%
“…Titanium dioxide films have demonstrated their capacity as a nano‐photocatalytic material, effectively decolorizing MB along with various other dyes and organic compounds [58] …”
Section: Resultsmentioning
confidence: 99%